Born in Bradford, a cohort study of babies born in Bradford, and their parents: Protocol for the recruitment phase - Raynor Pauline (BMC, 2008)
Abstract Background Bradford, one of the most deprived cities in the United Kingdom, has a wide range of public health problems associated with socioeconomic deprivation, including an infant mortality rate almost double that for England and Wales. Infant mortality is highest for babies of Pakistani origin, who comprise almost half the babies born in Bradford. The Born in Bradford cohort study aims to examine environmental, psychological and genetic factors that impact on health and development perinatally, during childhood and subsequent adult life, and those that influence their parents' health and wellbeing. This protocol outlines methods for the recruitment phase of the study. Methods Most Bradford women attend for antenatal care and give birth at the Bradford Royal Infirmary, which has approximately 5,800 births per year. Women are eligible for recruitment if they plan to give birth here. Babies born from March 2007 are eligible to participate, recruitment is planned to continue until 2010. Fathers of babies recruited are invited to participate. Women are usually recruited when they attend for a routine oral glucose tolerance test at 26-28 weeks gestation. Recruitment of babies is at birth. Fathers are recruited whenever possible during the antenatal period, or soon after the birth. The aim is to recruit 10,000 women, their babies, and the babies' fathers. At recruitment women have blood samples taken, are interviewed to complete a semi-structured questionnaire, weighed, and have height, arm circumference and triceps skinfold measured. Umbilical cord blood is collected at birth. Within two weeks of birth babies have their head, arm and abdominal circumference measured, along with subscapular and triceps skinfold thickness. Fathers self-complete a questionnaire at recruitment, have height and weight measured, and provide a saliva sample. Participants are allocated a unique study number. NHS numbers will be used to facilitate record linkage and access to routine data. A wide range of hospital and community sources is being accessed to provide data for the women and children. Data are checked for accuracy and consistency. Conclusion Born in Bradford will increase understanding of the factors that contribute to health and wellbeing, and identify factors that influence differences in them between people of Pakistani and European origin.